Development of Integrated Offline Learning Multimedia to Improve Student Learning Out Comes - Kuron, M A; Tompodung, M L (International Journal of Global Operations Research, 2020)
The research about development of integrated offline leaning multimedia aims to improve student learning outcomes and facilitate the learning process effect of use science materials teaching used multimedia software to improve students achievement. The subject of this research is VIIIB class with 22 numbers at Ranoyapo 2 State Junior High School. The research use Research and Delevopment (R & D) method with design by subject of experiment and seven models of development by Brog and Gall. This model consist of 7 step that are 1) Planning 2) Exploration study 3) Product development 4) Validation, 5) Data collection and analysis, 6) Product revition and 7) Dessimination. This integrated offline learning multimedia has been test by materials and media expert with questioner and has been revision. After that, the integrated offline learning multimedia has been tested by students in class VIIIB to known the student respons and student achievement with straight motion materials at sciences lesson. In the real class, students have given two treatments also called one period and two period. One period, students has teached by conventional models by commonly media used and Second period, students has teached used integrated offline learning multimedia that is research produce. The significant of normality by first period is 0.070 and the second is 0.133 is higher than the 0.05 of degree so that we conclusion that both of period are normal distribution. The analysed of this research used SPSS application be obtained significansi<0.05 so H0 is rejected and H1 is accepted, so the conclution said that there is a significant influence on student learning outcomes between teached by integrated offline leaning multimedia models and teached by conventional models.